Deflazacort vs prednisone treatment for Duchenne muscular dystrophy: A meta‐analysis of disease progression rates in recent multicenter clinical trials. Issue 1 (7th November 2019) - McDonald, Craig M.; Sajeev, Gautam; Yao, Zhiwen; McDonnell, Erin; Elfring, Gary; Souza, Marcio; Peltz, Stuart W.; Darras, Basil T.; Shieh, Perry B.; Cox, David A.; Landry, John; Signorovitch, James; et al.
Abstract: Introduction: In this study we characterized disease progression over 48 weeks among boys receiving deflazacort vs prednisone/prednisolone placebo arm treatment in two recent Duchenne muscular dystrophy (DMD) clinical trials. Methods: Ambulatory boys with DMD receiving placebo in the phase 3 ataluren (N = 115) and tadalafil (N = 116) trials were included. The trials required at least 6 months of prior corticosteroid use and stable baseline dosing. Associations between corticosteroid use and 48‐week changes in ambulatory function were estimated using mixed models. Adjusted differences between corticosteroid groups were pooled in a meta‐analysis. Results: In the meta‐analysis, deflazacort‐treated patients vs prednisone/prednisolone‐treated patients experienced, on average, lower declines of 28.3 meters on 6‐minute walk distance (95% confidence interval [CI], 5.7, 50.9; 2.9 seconds on rise from supine [95% CI, 0.9, 4.9 seconds]; 2.3 seconds on 4‐stair climb [95% CI, 0.5, 4.1 seconds]; and 2.9 [95% CI, 0.1, 5.8] points on the North Star Ambulatory Assessment linearized score). Discussion: Deflazacort‐treated patients experienced significantly lower functional decline over 48 weeks.